Desain Model Akselerasi Manajemen Sampah Sekolah Dasar sebagai Upaya Pembentukan Sekolah Berbudaya Lingkungan dan Pemberdayaan Ekonomi - Lita Dwipasari (University of Merdeka Malang, 2016)
Bank Sampah in Malang is an arm of government to manage waste. The more increasing number of quality garbage collected, the greater the customer's account at the Bank. Bank Sampah will help meet the waste demand of recycling plant. Elementary school is the customer target groups Bank Sampah Malang. They have many obstacles in its waste management activities. Bank Sampah and the Department of Education in Malang has been providing direction and some facilities for waste management in elementary schools. This study was conducted to produce a acceleration model of waste management Elementary School. Making design through several phases: analysis of the situation (questionnaire, observation and documentation). Structured questionnaire based on analysis Input-Process-Output (IPO). Evaluation model made through brainstorming to generate empirical models. Socialization and accompaniment is done at 3 elementary schools. Field testing is conducted through a quasi method because there are treatment methods for sample (Elementary School) . Final testing of this model is the descriptive analysis (changes of primary account number and environmental changes of elementary school) and inferential analysis by performing the Wilcoxon paired sample test (for non-parametric statistics). https://doi.org/10.26905/jmdk.v4i2.1065